Peran Kantor Urusan Agama dalam Menyikapi Pembebasan Kawin di Bawah Umur dan Syarat Nikah di KUA - Mirna Juwita; Mentari Mentari; Faza Lulu; Tengku Riski Muhammad; Shoufi Ramadhan; Wahyu Maulana; Maya Sari Siregar; Deliana Rambe (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
From the research results, the main problem with the role of the Bureau of Religious Affairs is that there are many exemptions for marriage/early marriage. Early marriage refers to married couples who are underage. That's what it says in the Indonesian law on the admissibility of marriage, the age limit is 16 years old, which was the previous requirement, which is not in the law.